3-D physiomimetic extracellular matrix hydrogels provide a supportive microenvironment for rodent and human islet culture. (April 2019) - Jiang, K.; Chaimov, D.; Patel, S.N.; Liang, J.-P.; Wiggins, S.C.; Samojlik, M.M.; Rubiano, A.; Simmons, C.S.; Stabler, C.L.
Abstract: Organ-on-a-chip platforms serve as cost-efficient testbeds for screening pharmaceutical agents, mimicking natural physiology, and studying disease. In the field of diabetes, the development of an islet-on-a-chip platform would have broad implications in understanding disease pathology and discovering potential therapies. Islet microphysiological systems are limited, however, by their poor cell survival and function in culture. A key factor that has been implicated in this decline is the disruption of islet-matrix interactions following isolation. Herein, we sought to recapitulate the in vivo peri-islet niche using decellularized extracellular matrix (ECM) hydrogels. Sourcing from porcine bladder, lung, and pancreas tissues, 3-D ECM hydrogels were generated, characterized, and validated using both rodent and human pancreatic islets. Optimized decellularization protocols resulted in hydrogels with distinctive viscoelastic properties that correlated to their matrix composition. The in situ 3-D encapsulation of human or rat islets within ECM hydrogels resulted in improved functional stability over standard culture conditions. Islet composition and morphology were also altered, with enhanced retention of islet-resident endothelial cells and the formation of cord-like structures or sprouts emerging from the islet spheroid. These supportive 3-D physiomimetic ECM hydrogels can be leveraged within microfluidic platforms for the long-term culture of islets.